Comparative Analysis of Seventeen Mitochondrial Genomes of Mileewinae Leafhoppers, Including the Unique Species Mileewa digitata (Hemiptera: Cicadellidae: Mileewinae) From Xizang, China, and New Insights Into Phylogenetic Relationships Within Mileewini - Hongli He; Bin Yan; Xiaofei Yu; Maofa Yang (Ecology and Evolution)
ABSTRACT The subfamily Mileewinae in China comprises one tribe (Mileewini), four genera (Ujna, Mileewa, Processina, Anzihelus), and 71 species, yet only 11 mitochondrial genomes have been published. This study aimed to elucidate ambiguous diagnostic traits in traditional taxonomy and examined phylogenetic relationships among genera by sequencing mitochondrial genomes from 16 species. The lengths of the mitochondrial genomes ranged from 14,532 to 15,280 bp, exhibiting an AT content of 77.2%–80.7%, indicative of AT bias. Each genome contains 13 protein‐coding genes (PCGs), 22 transfer RNA genes (tRNAs), and 2 ribosomal RNA genes (rRNAs). Notably, the genome of the Xizang endemic Mileewa digitata measures 15,280 bp, with an AT content of 80.7%, 10,941 bp of PCGs, and a 949 bp control region (CR) followed by a 19 bp poly‐A tail. Gene arrangement among the 17 genomes mirrors that of other Mileewinae species. Analyses of nucleotide diversity and evolutionary rates indicate purifying selection on PCGs, with atp8 exhibiting the greatest variability and evolutionary rate, whereas cox1 shows the least. Genetic distance studies display minimal separation among Mileewa species, specifically Mileewa nii with Mileewa margheritae and Mileewa rufivena with Mileewa ussurica, as well as the two morphs of Mileewa digitata. Phylogenetic analyses using Bayesian Inference (BI) and Maximum Likelihood (ML) generated six trees, further questioning the monophyly of the genera Mileewa, Ujna, and Processina. The reconstructed ancestral state based on the forewing patch position suggests that the common ancestor of Chinese Mileewini species was situated exclusively on the costal margin, prompting a proposed division of the tribe's species into two categories (genera). This research enriches the understanding of phylogenetic relationships within Mileewinae and contributes to the mitochondrial genome database for this group, paving the way for future taxonomic studies in China.